Reflections on Two Centuries of Western Women’s Writing about Sikhs - Nesbitt, Eleanor (Religions of South Asia, 2019)
Dorothy Field is the one woman whose writing appears in major anthologies of European writing on Sikhs and their religion. Although Field’s 1914 monograph was the first substantial study of Sikhism by a western woman, since early in the nineteenth century many other women have also commented on Sikh history, religion and society and described their face-to-face encounters in India (and, more recently, in the UK). For the purposes of this article, western women who have converted to Sikhism and western academics in Sikh Studies (in the late twentieth and early twenty-first centuries) have been omitted. Instead, this article introduces some of the female diarists, letter-writers, novelists and royals who have written about Sikhs and proceeds to illustrate three of their recurrent themes: the ‘transformation’ of the religion of Baba Nanak by later Gurus; the matter of ‘idolatry’ and, connected with this, the relationship of Sikhs to ‘Hinduism’. The relevance of ethnography-both to my interrogation of the women’s output and to their reporting of their engagement with Sikhs-is also considered, as is the nature of the friendships between western women and Sikhs.